Adaptive Practices of Millennial Teachers in Technology Integration at a Rural Elementary School: A Case Study of SDN 182 Angin-Angin - Said, Rahmat (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This study explored the adaptive practices of millennial teachers in integrating technology into learning at SDN 182 Angin-Angin, a rural elementary school in Enrekang Regency. The study focused on technology-based instructional strategies, enabling and constraining factors, and observable student engagement during learning. A qualitative descriptive-exploratory case study design was employed. Data were collected through semi-structured interviews with teachers who met the study criteria, classroom observations, and instructional-document analysis, and were examined thematically through data reduction, display, and verification. Trustworthiness was supported through source and method triangulation, member checking, peer debriefing, and an audit trail. The findings show that teachers used blended learning, flipped classroom, gamification, microlearning, Quizizz, YouTube, e-modules, and visual media to create more interactive learning experiences. Unstable internet access, limited devices, restricted access to paid applications, and insufficient technology training were addressed by downloading materials in advance, combining digital and printed resources, independent professional learning, and peer collaboration. Classroom observations indicated stronger engagement, curiosity, and participation among students. The findings suggest that digital transformation in rural elementary schools depends not only on infrastructure but also on teachers’ adaptive capacity and pedagogical decision-making.